Arka Aadya and Arka Archana: new China aster varieties - Kumar, Rajiv; Rao, T. Manjunatha; Janakiram, T (Indian Horticulture, 2019)
New varieties, Arka Aadya and Arka Archana of China aster are floriferous, early-flowering and high flower yielding. They produce more number of branches and flowers/plant, with extended blooming period. They have field tolerance to lodging and do not require additional staking. They are recommended for loose flower (flower with short stalk) production and growing for bedding purpose.